PHYSICAL PROPERTIES, DIGESTIBILITY AND METABOLITE PRODUCTS IN-VITRO FROM BIOSUPPLEMENTS USING LINOCELLULOLITIC BACTERIAL BIOCATALYSTS - M. F., Rohman; Partama, I. B. G.; Mudita, I. M. (Jurnal Peternakan Tropika; Vol 9 No 1 (2021): Vol. 9 No. 1 Tahun 2021; January - april, 2021)
This study aims to determine the physical properties, digestibility, and metabolite products in-vitro of biosupplements using lignocellulolytic bacterial biocatalysts. This study was conducted at the Sesetan Farm and the Laboratory of Animal Nutrition and Forage, Faculty of Animal Husbandry, Udayana University, which was conducted from January to March 2020. The design used was a completely randomized design (CRD) consisting of 6 treatments, namely biosupplement without biocatalysts of lignocellulolytic bacteria as control (BS0) , using the bacterium Bacillus substilis BR4LG (BS1) biocatalyst, using the bacterial Bacillus substilis BR2CL (BS2) biocatalyst, using the Aneurinibacillus sp. bacterial biocatalyst. BT4LS (BS3), using a bacterial biocatalyst Bacillus sp. BT3CL (BS4), and using a bacterial biocatalyst Bacillus sp. BT8XY (BS5). Each treatment had 3 replications. The variables observed were physical properties, digestibility, and metabolite products. Data were analyzed using variance. The results showed that quantitative BS2 treatment resulted in the highest density and water absorption of 0.50 g / ml and 135.05%, respectively (P> 0.05) and resulted in the highest KcBK of 71.07% (P <0 , 05). The BS3 treatment resulted in the highest KcBO and VFA total, respectively 71.35% and 189.89 mM (P <0.05). BS4 treatment resulted in the highest N-NH3 of 16.73 mM (P <0.05). Quantitative BS5 treatment resulted in water solubility of 75.27% (P> 0.05). Based on the results of the study, it can be concluded that the use of lignocellulolytic bacterial biocatalysts could not improve physical properties, but was able to increase the in-vitro digestibility of dry matter and organic matter and metabolite products (VFA and N-NH3) from biosupplements. The best bacterial biocatalyst in this study was Aneurinibacillus sp. BT4LS for being able to produce the highest KcBO and VFA Total.   Keywords:   lignocellulolytic bacterial biocatalys, biosupplement, digestibilyty, rumen fermentation products , and physical characteristics